Meningkatkan Kemampuan Memahami Konsep Bilangan 1-10 Dengan Kartu Angka Melalui Metode Demonstrasi Pada Anak Didik Kelompok B TK Bakti Mulia Tlepokkulon - Dwi Oktariyanti (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2022)
This research was conducted on the grounds that group B students at Bakti Mulia Kindergarten Tlepokkulon had low cognitive abilities. The purpose of this study was to describe the effect of using number card media in improving students' cognitive abilities. This research uses classroom action research which is carried out in three cycles and each cycle through planning, implementing actions, observing, and reflecting. The subjects of this study were group B students of Bakti Mulia Kindergarten, Tlepokkulon Village, Grabag District, Purworejo Regency, which collected 15 children. The object of the research is to increase children's cognitive abilities in understanding the concept of numbers with number symbols using number cards as media. The results showed an increase in children's cognitive abilities through the connection of a collection of objects 1-10 with number cards through the demonstration method, namely students who developed according to expectations which previously reached 2 children (13%), in the cycle to 4 children (27%), cycle 2 became 7 children (46%) and cycle 3 became 13 children (86%).